Potential of middle managers: assessment methodology - А. А. Dolgaya (Вестник университета, 2025)
The purposes of the study are to create and test a set of methods for assessing the potential of a middle-level manager in a medical institution in order to make further recommendations for their development. To achieve this, a methodology has been developed based on the case of a private medical institution. The main data has been collected by interview, 360-degree assessment and tests. The author justifies the reasons to apply a group of methods defined as contextual analysis: gamba observation, analysis of critical incidents and causal analysis. Verification and interpretation of the obtained signs is conducted using the Signs vs Samples method. The methodology has been tested on the case of a private medical centre. The data obtained by the 360-degree assessment and self-assessment interviews are largely contradictory. Testing on the basis of Myers-Briggs typology has served as an effective tool for reconciling the contradictions. The contextual analysis has revealed the facts used furtherly to verify the data characteristics and interpret the results. It is found that the potential of a middle-level manager depends on the attitude of a higher-level manager towards them. The proposed methodology can be used in other medical organisations to plan the development trajectory of middle managers.